Establishment and Development of Mining Rescue in Russia - Dubrovskaya, Yu. A. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The underground mining method is associated with special working conditions that are unfriendly to humans: cramped space, lack of light, high humidity, gas pollution, constant stress, dirt, artificial ventilation, self-ignition, special microclimatic conditions, heavy physical and psychological stress. These factors are constantly affecting miners underground. Special mining measures are required to minimize dangerous situations, but first of all, professional training of mining rescue engineers. Goal. The study aims to analyze the main factors that influenced the origin of the Russian mountain rescue service; to reveal the stages of formation and development of the mining business in Russia; to identify problematic issues of personnel training for the Russian mountain rescue service. Materials and methods. To achieve this goal, the research used theoretical and system-structural methods: historical – analysis of the history of the formation and development of the mining rescue service; system-structural method in order to identify the components and relationships that ensure the formation of the mining rescue business in Russia. Results and discussion. Based on the analysis of the documents, the key stages of the formation and development of the mining business in Russia are shown: from the first specialized mountain rescue station in Makeyevka, to the modern structure of paramilitary mountain rescue units that are part of the Russian Ministry of Emergency Situations. Conclusion. By their nature, mining operations are potentially dangerous and accidents cannot be completely avoided. But it is necessary to train specialists to deal with emergencies and minimize the consequences of mining accidents and catastrophes